Influence of the vibration source location on the modes of jet disintegration in the priller and on monodispersity of the finished product - Skydanenko, Maksym; Kononenko, Mykola; Kurdes, Yuliia (Видавництво Львівської політехніки, 2017)
Influence of the vibration source location on the modes of liquid jets disintegration and obtaining monodisperse droplets and granules of the finished product is theoretically grounded and experimentally confirmed. The experiment was conducted on an experimental stand of industrial granulation equipment.
Keywords: forced perturbations; priller; regular hits; jet disintegration; monodispersity; satellite droplets